Effect Of The Number Of Packaging Perforations On The Quality Of Lettuce Vegetables (Lactuca sativa L.) at Room Temperature Storage - Aisah, Siti; Ayunita, Farrah; Anwar, Ivan Fauzi; budirokhman, dodi (Jurnal Agrosci, 2025)
Background. After harvesting and during storage, lettuce is prone to quality deterioration, so the post-harvest process must be considered to maintain its quality and shelf life. Aim. This study aims to determine the effect of the number of perforations on packaging on the quality of lettuce (Lactuca sativa L.) during room-temperature storage. Methods. This research was conducted in the Laboratory of the Faculty of Agriculture, Gunung Jati Independent University, Cirebon, West Java. This research was conducted in July 2024. This study used a Complete Random Design (RAL) with 5 (five) treatments repeated 5 times. The variables observed were weight loss, moisture content, damage rate, and vitamin C levels. Result. The P3 treatment (4-hole perforation) is the best treatment for the quality of lettuce vegetables (Lactuca sativa l.) stored at room temperature. Conclusion. Based on the research results, the number of perforations has a real influence on weight loss parameters, moisture content, and damage rate. However, it has no effect on vitamin C levels in lettuce vegetables. Implementation. The best treatment was found at P3 (perforation 4), with the lowest percentage of weight loss, high moisture content, and the lowest level of damage at each observation.